PENENTUAN MODEL RANCANGAN OPTIMUM TATA LETAK (LAYOUT) AREA PARKIR SEPEDA MOTOR (Studi Kasus: Universitas Esa Unggul) (Universitas Esa Unggul, 2017)
The purpose of this research is to determine the optimum design model of motorcycle parking area layout at EsaUnggul University. The first step in this research is to know the value of parking accumulation (AP), parking volume (VP), parking capacity (N) and parking index (IP) of motorcycle parking area used in EsaUnggul University today. Based on observations, the parking capacity of the rear parking area is currently 1085 motorcycles and for the front parking area of 250. For the need for parking area based on the highest parking accumulation of the number of motorcycles located in the rear parking area as much as 1309 motorcycles and in front parking area 288 motorcycles. There is still a difference of 224 for the rear parking area and 38 on the front parking area. Furthermore, for the second phase, the design of the model for the rear parking area and front. From the design results there are 7 models of the design model produced for the motorcycle parking area owned by EsaUnggul University which consists of 5 design models for rear parking area and 2 design models for front parking area. For the design of the rear parking area model is the modification of current parking conditions, angle patterns 90°, 60°, 45°, and 30°. As for the design of the front parking area model is the modification of current parking conditions and the combination of angle patterns 60° and 90°. The calculation of the parking index (IP) of each model design indicates that IP > 1 which means the parking requirement exceeds the parking area capacity. From the results of this research, the optimum model design is angle 90° for rear parking area and combination of angle pattern 60° and 90° for front parking area. It is expected that the results of this design obtained regularity in the parking of motorcycles, reducing complaints motor damage, increasing the convenience of parking facilities and facilities users lack of congestion for the in and out of the parking area, because the plot has been set. Keywords: parking, perking area, parking accumulation (AP)